Association Between Caregiver’s Nutrition Knowledge and Nutrition Status of Children 6 to 23 Months: A Case Study of Narok County Referral Hospital - Nkoitoi, Sheillah; Chege, Peter; Walekhwa, Michael (AFRICAN JOURNAL OF NUTRITION AND DIETETICS, 2024)
In Narok County, Kenya, where the challenge of achieving optimal child nutrition persists, particularly in the context of its arid and semi-arid climate, the prevalence of stunting among children is alarmingly high compared to other regions. Addressing this critical issue necessitates an enhancement of caregivers’ nutrition knowledge. However, scant information is available on the nutritional knowledge of caregivers responsible for children aged 6 to 23 months, a gap that extends beyond Narok County to encompass broader regions in Africa, including Kenya. Consequently, this study was designed to examine the nutritional knowledge of caregivers within Narok County for children in this age group. All approvals including ethical clearance from Kabarak University Research and Ethics Committee (KUREC), research permit from NACOSTI and permit from Narok County Referral Hospital were sought before commencement of the study. This research adopted a descriptive cross-sectional design, and fisher’s formula was used to calculate a sample size of 108 caregivers to children aged 6 to 23 months who were purposively recruited. Data were analysed using SPSS version 25 and ENA SMART soft wares. The results indicate a variation in caregivers’ nutrition knowledge levels, with 37.0% demonstrating a high level of knowledge, while 27.8% exhibited low knowledge. Moderate knowledge levels were observed in 14.8% of caregivers, while 9.3% had very low knowledge. Furthermore, there was a low positive correlation observed between nutrition knowledge and Height-for-Age Z-score (HAZ), with a correlation coefficient of r=0.235 and a p-value of 0.014. Significantly, HAZ exhibited a higher percentage of normal scores when compared to stunted children (p-value: 0.05*). In conclusion, the study found significant variation in caregivers’ nutrition knowledge across the region, which in turn had an impact on the nutritional outcomes of the children. Therefore, we recommend targeted and continuous nutrition education to care-givers of children in Narok County. Caregivers with better nutrition knowledge tend to provide better nutrition to their children. There is need to train and capacity build community health workers to have necessary knowledge and skills for effective nutrition education.
Keywords: caregivers; children; 6-23 months; nutrition knowledge